2022
DOI: 10.3390/nu14030722
|View full text |Cite
|
Sign up to set email alerts
|

Gut Seasons: Photoperiod Effects on Fecal Microbiota in Healthy and Cafeteria-Induced Obese Fisher 344 Rats

Abstract: Gut microbiota and biological rhythms are emerging as key factors in the modulation of several physiological and metabolic processes. However, little is known about their interaction and how this may affect host physiology and metabolism. Several studies have shown oscillations of gut microbiota that follows a circadian rhythmicity, but, in contrast, variations due to seasonal rhythms have not been sufficiently investigated yet. Thus, the goal of this study was to investigate the impact of different photoperio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
2
17
0
2
Order By: Relevance
“…In this context, GSPE decreased the photoperiod effect observed on the fecal microbiota composition in VH-treated rats, showing similar beta- and alpha-diversity independent of photoperiod conditions, and modulating the most abundant genera. Accordingly, Bacteroides , Oscillospira , Coprococcus and Ruminococcu s genus levels, which were associated with higher BW gain and fat depot accumulation under L18 conditions in VH-treated rats, 28 did not show any photoperiod effects in GSPE-treated rats. Therefore, GSPE affected BW gain and the gut microbiota composition in a photoperiod dependent manner, suggesting a potential interaction among GSPE, the gut microbiota and photoperiod conditions.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this context, GSPE decreased the photoperiod effect observed on the fecal microbiota composition in VH-treated rats, showing similar beta- and alpha-diversity independent of photoperiod conditions, and modulating the most abundant genera. Accordingly, Bacteroides , Oscillospira , Coprococcus and Ruminococcu s genus levels, which were associated with higher BW gain and fat depot accumulation under L18 conditions in VH-treated rats, 28 did not show any photoperiod effects in GSPE-treated rats. Therefore, GSPE affected BW gain and the gut microbiota composition in a photoperiod dependent manner, suggesting a potential interaction among GSPE, the gut microbiota and photoperiod conditions.…”
Section: Discussionmentioning
confidence: 81%
“…Isolated DNA was quantified using a NanoDrop ND2000 spectrophotometer (Thermo Fisher Scientific, Massachusetts, USA) and used for 16S ribosomal RNA sequencing using an Ion S5 system (Life Technologies, California, USA) as described previously. 28…”
Section: S Rrna Analysismentioning
confidence: 99%
“…Moreover, the gut microbiota rapidly responds to an obesogenic environment, where its composition is altered. A recent study revealed that the impact of photoperiod in fecal bacteria was accentuated in cafeteria-fed rats [ 93 ]. In fact, the obesity-derived alterations in the fecal microbiota were exaggerated in animals housed under long photoperiod conditions [ 93 ].…”
Section: Impact Of Obesity In the Photoperiodic Remodeling Of Adiposi...mentioning
confidence: 99%
“…Interestingly, our group reported that biological rhythms can influence both gut microbiota [ 33 ] and polyphenols bioactivities [ 34 , 35 ]. Remarkably, we recently reported that photoperiod can influence the functionality of one grape seed proanthocyanidin extract (GSPE) via gut microbiota [ 36 ].…”
Section: Introductionmentioning
confidence: 99%